Analysis of Optimal Stock Portfolio Formation Using the Single Index Model Approach for Investment Decisions - Dewi Manggar Sari; Mutiara Audina; Carina Fantasia (AIBPM Publisher, 2025)
The aim of this research is to explore the composition that results in an optimal investment portfolio from stocks listed in the IDXQ30 index using the Single Index Model (SIM). This research Time Frame covers January 2021 to December 2024, with 14 consistently listed stocks identified as the initial sample. According to the calculation of Excess Return to Beta (ERB) and the determination of the cut-off point (C*), six stocks were selected as portfolio candidates, namely BMRI, BBCA, UNTR, PTBA, CPIN, and ACES. The final results presented in the optimal weighting table reveal that only four stocks are belong to the optimal portfolio, comprising BMRI, BBCA, UNTR, and PTBA. The greatest portion of the fund allocation was achieved by BMRI at 44.43%, followed closely by BBCA at 44.06%. In contrast, UNTR and PTBA contributed smaller weights of 7.33% and 4.18%, respectively. This composition indicates that the financial sector, represented by BMRI and BBCA, dominates the optimal portfolio, while other sectors provide additional diversification. These findings emphasize that stocks with the highest efficiency in generating returns relative to risk are prioritized in portfolio construction, thereby producing an allocation that balances return potential and risk exposure.